Digital marketing training to increase the marketing of MSME products in the Banua Anyar Village - Muhammad Rezky Noor Handy; Syaharuddin Syaharuddin; Ismi Rajiani; Muhammad Adhitya Hidayat Putra; Risna Putra Pradana; Resty Nurqomah (Community Empowerment, 2024)
The COVID-19 pandemic has caused a significant decline in sales for MSMEs, especially those relying on conventional sales methods. This community service aims to provide digital marketing training to enhance the marketing of UMKM products in Kelurahan Banua Anyar, Banjarmasin City. The training consisted of two parts: firstly, discussions and presentations on online marketing strategies for UMKM products, and secondly, hands-on training on technology and applications to support online sales. This program was able to provide convenience for MSMEs to expand market access for their products, especially with increased knowledge about digital marketing and skills in utilizing social media and product photography.